PENGARUH SGLT-2 INHIBITOR TERHADAP TEKANAN DARAH DAN ALBUMINURIA PADA PASIEN DIABETES MELITUS TIPE 2 DENGAN HIPERTENSI: TELAAH SISTEMATIK - Fatimah Azzahra (2022)
Introduction:. The presence of hypertension as a comorbid disease in type 2 diabetes mellitus (DM) patients can increase the risk of mortality, morbidity, and disability. SGLT-2 inhibitors are second-line antidiabetic drugs indicated in patients with comorbid atherosclerotic cardiovascular disease, chronic kidney disease with a record glomerular filtration rate (GFR) > 60 ml/min, etc., which have been shown to have a positive effect on blood pressure and albuminuria. A review to see whether or not there is a positive effect of SGLT-2 inhibitors on blood pressure and albuminuria in type 2 DM patients with hypertension is needed to determine the optimal treatment option. Methodology: This systematic review was carried out by reviewing several studies on the PubMed, ScienceDirect, Google Scholar, and EBSCOhost databases based on inclusion and exclusion criteria. The studies obtained will then be selected using the PRISMA-P 2020 method and tested for quality using JBI Critical Appraisal Tools in accordance with the research design of the study obtained. Results: From the 7 articles obtained, 4 articles of 6 articles that discussed the effect of SGLT-2 inhibitors on blood pressure showed significant results and 1 articles of 2 articles that discussed the effect of SGLT-2 inhibitors on albuminuria showed significant results . The types of SGLT-2 inhibitors used from the 7 articles were quite varied, namely canagliflozin, empagliflozin, and dapagliflozin. Conclusion: SGLT-2 has been proven to have a positive effect on blood pressure and albuminuria. This can be a consideration for giving SGLT-2 inhibitors as a combination therapy in type 2 DM patients with hypertension.